If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-25)(x+24)=0
We multiply parentheses ..
(+x^2+24x-25x-600)=0
We get rid of parentheses
x^2+24x-25x-600=0
We add all the numbers together, and all the variables
x^2-1x-600=0
a = 1; b = -1; c = -600;
Δ = b2-4ac
Δ = -12-4·1·(-600)
Δ = 2401
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{2401}=49x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-49}{2*1}=\frac{-48}{2} =-24x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+49}{2*1}=\frac{50}{2} =25
| (x-25)(x+24)=6000 | | 7/2x=5/6 | | 18f-20f+18=-4f-10 | | (x-25)(x+24)=600 | | (x-25)(x+13)=325 | | 1=-1+t6 | | 19x=-12x | | 25=-2r+3 | | -9.1d+10.8=6.02-2.2d+19.96 | | 9=3(q+8) | | -h-18=18+4+4h | | -6q-1+7q=2q+14 | | 4=2/3(r-6) | | 3x+7x=-70 | | 8+14b-b=12b-8 | | 7(b+3)+5(b+9)=1 | | 7q+16=44 | | -5x+x/7=-3 | | -17=n-7/3 | | -7(y+4)=-5y-3 | | 5(4z+5)=8z+1 | | v2+16=20 | | 7(3n+5)=7n+4 | | w+10/4=4 | | 8y+5(5y-6)=16 | | 9b+2(5b-5)=13 | | 6a+4(5a-7)=15 | | (n-1)^2=0 | | 14x+67=7x+50 | | w+104=4 | | x+x*0.2=890 | | -5(c+5)=-20 |